Media Relations Strategy of the Ministry of Environment and Forestry and the Ministry of Defense in Detecting Hoax News in Online Media - Kania Dafina; Lely Ika Mawarti; Hudi Santoso; Wahyu Budi Priatna; Suparman Suparman; Guruh Ramdani (Jurnal Mamangan, 2024)
One of the media relations activities is media monitoring. Media monitoring is a form of activity carried out by the Public Relations Bureau in companies and government agencies. The rise of various hoax reports in various media, especially online media, makes it necessary to monitor media through media monitoring activities. The aim of this research is to describe media relations strategies in overcoming the spread of hoax news through media monitoring. The theory used in this research is the Comcowich theory, which is related to media monitoring strategies, using descriptive qualitative research methods. The difference between this research and previous research lies in the research objects used, namely the Ministry of Environment and Forestry and the Ministry of Defense, and this research focuses on the spread of hoax news, which in previous research no one had used so that something new emerged. The results of this research show that the Public Relations Bureau of the Ministry of Environment and Forestry and the Ministry of Defense have a strategy to overcome the spread of hoax news, namely that the Public Relations Bureau of the Ministry of Environment and Forestry uses a paid site called Intelligence Media Analytics (IMA) and media clipping. Meanwhile, the Ministry of Defense's Public Relations Bureau also uses three media monitoring techniques, namely media tracking, media clipping and media content analysis.